2021
DOI: 10.3390/healthcare9070918
|View full text |Cite
|
Sign up to set email alerts
|

Can Residential Greenspace Exposure Improve Pain Experience? A Comparison between Physical Visit and Image Viewing

Abstract: Reducing the burden of pain via greenspace exposure is a rising research topic. However, insufficient evidence has been found in relation to the environmental effect itself. Residential greenspace, as a convenient but limited natural environment for urban dwellers, has benefits and services yet to be discovered. Therefore, the current study recruited 24 young adults to evaluate the effects of physical visit to, or image viewing of, residential greenspace on pain perception and related psychophysiological outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 64 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Specifically, a study reported the positive effect of virtual nature on cognitive performance ( Mostajeran et al, 2021 ), which could be related to its restorativeness ( Shin, 2011 ). Tanja-Dijkstra et al (2018) reported that virtual nature reduced both experienced and recollected pain during simulated pain, which is broadly in line with the recent findings on pain relief and actual nature exposure ( Stanhope et al, 2020 ; Li et al, 2021a ). Drawing from previous studies, pain relief could result from both the distraction of VR itself and the audiovisual stimuli of nature ( Kline, 2009 ; Sil et al, 2014 ; Guo et al, 2015 ).…”
Section: General Effects Of Virtual Naturesupporting
confidence: 85%
“…Specifically, a study reported the positive effect of virtual nature on cognitive performance ( Mostajeran et al, 2021 ), which could be related to its restorativeness ( Shin, 2011 ). Tanja-Dijkstra et al (2018) reported that virtual nature reduced both experienced and recollected pain during simulated pain, which is broadly in line with the recent findings on pain relief and actual nature exposure ( Stanhope et al, 2020 ; Li et al, 2021a ). Drawing from previous studies, pain relief could result from both the distraction of VR itself and the audiovisual stimuli of nature ( Kline, 2009 ; Sil et al, 2014 ; Guo et al, 2015 ).…”
Section: General Effects Of Virtual Naturesupporting
confidence: 85%
“…There are many other examples emerging for the harm reduction domain pathway that have potential synergies with other pathways. For example, it is plausible that restorative processes at personal, relational and collective scales combine with lower levels of neighbourhood violence and increased social connection to facilitate reductions in pain, [166][167][168] cigarette smoking, 169 opioid dependence, 170 substance misuse in adolescents, 171 and risks of self-harm and suicidal ideation. [172][173][174][175] Each of these emerging harm reduction pathways warrant further investigation, potentially with moderated mediation models and other methods that may be suitable to distinguish between pathways operating in serial or parallel.…”
Section: Domain 1: Building Capacitiesmentioning
confidence: 99%
“…There were seven different types of outdoor intervention; however, over half of the studies were one-day forest therapy interventions [14,16,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Other studies included mountaineering expeditions [41][42][43][44], forest therapy camps [45][46][47][48], green exercise [49][50][51][52], blue exercise [53], horseback riding [54], and skydiving [55]. Over half of the control groups had a similar exposure type as the intervention but in an urban context.…”
Section: Methods Characteristicsmentioning
confidence: 99%
“…Almost every study used other physiological or psychological measures in their study, however five studies did not report the use of any other measures [29,32,45,46,57]. The three physiological measures that were most recorded included blood pressure (Bp) [28,31,[34][35][36]38,[40][41][42]49,50,52,53,58], heart rate (Hr) [28,30,38,39,42,43,[47][48][49][50]55,56,59,60], and salivary cortisol [33,37,[39][40][41][42]44,47,49,51,54,58]. Other less common physiological measures assessed were pulse rate (PR) [31,36,41,53,…”
Section: Additional Physiological and Psychological Measuresmentioning
confidence: 99%
See 1 more Smart Citation